100‐Layer Error‐Free 5D Optical Data Storage by Ultrafast Laser Nanostructuring in Glass. Issue 4 (23rd January 2022) - Wang, Huijun; Lei, Yuhao; Wang, Lei; Sakakura, Masaaki; Yu, Yanhao; Shayeganrad, Gholamreza; Kazansky, Peter G.
Abstract: The demand for energy efficient data storage technologies with high capacity and long life span is increasingly growing due to the explosion of digital information in modern society. Here, a 5D optical data storage with high capacity and ultralong lifetime is realized by femtosecond‐laser‐induced anisotropic nanopore structures (type X modification) in silica glass. The ultrahigh transmission of this birefringent modification, >99% in the visible range, allows recording and retrieving thousands of layers of multibit digital data practically. Type X formation is associated with moderate free carrier density produced close to the energy threshold of avalanche ionization. Higher retardance with increased repetition rate at low pulse energy is attributed to accumulation of defects (nonbridging oxygen hole centers), enabling rapid imprinting of voxels by megahertz‐rate pulses. Data recording of 7 bits per voxel, i.e., 2 5 azimuth angles and 2 2 retardance levels is experimentally demonstrated with readout error as small as 0.6%. Furthermore, "The Hitchhiker's Guide to the Galaxy" by Douglas Adams is optically recorded with a data writing speed of 8 kB s −1 in 100 layers of voxels and the proven data readout accuracy of 100%. Abstract : 100‐layer 5D data storage with 100% readout accuracy and writing speed of 8 kB s −1 is demonstrated by femtosecond‐laser‐induced ultralow‐loss modification with flattened nanopores in silica glass. Anisotropic nanopore formation is associated with moderate free electron density produced with pulse energy close to the threshold of avalanche ionization.